Man's best friend(s): Effects of a brief befriending meditation on human-animal relations. - Otto Simonsson; Simon B Goldberg; Walter Osika (PLoS ONE, 2022)
In two studies using samples representative of the US adult population with regard to age, sex and ethnicity, we investigated relationships between loving-kindness and compassion-based practices with speciesism, animal solidarity and desire to help animals. In a cross-sectional study (Study 1, N = 2,822), results showed that past 30 days practice and estimated lifetime number of hours of lovingkindness or compassion meditation were associated with more animal solidarity and greater desire to help animals. Past 30 days practice was also associated with less speciesism, but only when adjusting for sociodemographic characteristics. In an experimental study (Study 2, N = 1,102), results showed that participants randomized to a befriending meditation (a practice similar to loving-kindness and compassion meditation) condition scored higher on animal solidarity and desire to help animals than participants randomized to a control condition. No significant difference was observed on speciesism, but mediation analyses suggested that effects on all three outcomes were mediated through perceived commonality with animals.